ANALISIS PENGGUNAAN IDIOM DALAM BERITA KRIMINAL SURAT KABAR HARIAN JAMBI INDEPENDENT EDISI JUNI 2013 - Leni Safrika; Warni Warni; Andiopenta Purba (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
The method used in this research is qualitative method with descriptive type of approach. Source of research data is a daily newspaper Jambi Independent. Data collection technique used wancana analysis techniques which refer to the semantic analysis. Checking the validity of the data using the triangulation method and theory. Research conducted on Jambi Independent idiom in the daily edition of June 2013, found forty-eight (48) idiom in crime news of forms namely: form words (18 idioms) and the form of the phrase (30 idiom). Based on these results it can be concluded that the use of idioms in crime news is still often used in the form of words and phrases. If the terms of the idiom meaning it can be stated that the use of idioms in crime news daily Independent Jambi June 2013 edition is used as a meaning which tends to lead to the situation, stated objects, places, people and jobs (activities). Based on the research results presented some suggestions that can be expected of government and journalists should use simple words or language that is easily digested by the public. This study aims to assess the use of idioms in Jambi Independent Daily newspaper edition in June 2013 to determine the form and meaning of idioms contained in Jambi Independent daily newspaper June 2013 edition.